Knowledge and Practices of Vegetables Insect Pest Managements in Banganga Municipality of Kapilvastu District - Ghimire, P; Sah, L P; Gyawali, S (Journal of the Plant Protection Society, 2022)
A study was carried out in Banganga Municipality of Kapilvastu district to know the farmer’s knowledge, practices, and management method used in insect pests of vegetables. The survey involved 160 randomly selected farmers who were interviewed using semi-structured questionnaires and also evaluated based on direct field observation. The data were analyzed using SPSS and Microsoft-Excel. Tomato, potato, chili, cauliflower, cabbage, garlic, and onion were major vegetables grown by the farmers during the winter season and cucumber, bottle gourd, bitter gourd, sponge gourd, tomato, chili, brinjal during the summer season. Aphids, cabbage butterfly, pumpkin beetle, tomato leaf miner, cutworm, and tomato fruit borer were the major pests in vegetable field. Knowledge of vegetable farmers regarding insect pest identification was also observed i.e., 86% of respondents identified insect pest by the help of Junior Technical Assistance and agro-vets, and 10% of respondents identified insects by their own knowledge. About 60% of respondents were found using chemical pesticides such as; chlorpyrifos, cypermethrin, imidacloprid, alphamethrin etc. to control pests, 4% of respondents were using botanical plant extract i.e., jholmal, neem extract, cow urine and 24% were using cultural methods such as crop rotation, mulching, tillage operation. Only a few farmers’ groups were found to know about IPM, biological pest management practices, and conservation of natural enemies.